THE ROLE OF IMAGINATIVE PLAY AND INHIBITORY CONTROL TOWARDS PROSOCIAL BEHAVIOR IN PRESCHOOL CHILDREN: Peran Permainan Imajinatif dan Kontrol Inhibisi pada Perilaku Prososial Anak Usia Prasekolah - Fina Melinda Purba,; Efriyani Djuwita,; Inge Uli Wiswanti, (Jurnal Ilmu Keluarga dan Konsumen, 2024)
Preschool age is a crucial period to foster children's prosocial behavior using imaginative play. This study aims to determine the relationship between imaginative play and prosocial behavior, with inhibitory control as a moderator. The instruments used are the Strengths and Difficulties Questionnaire (SDQ) dimensions of prosocial behavior, the Child Imagination Questionnaire (CIQ), and Head-Toes-Knees-Shoulders Task. Participants were preschool children aged 3–6 years (n = 75). Parents and teachers of children are also involved in administering the data. The results show that there are differences in the assessment results between teachers and parents. The teachers' assessment result shows a significant relationship between imaginative play and prosocial behavior [(75)=0.501, p